Thrombolysis for ischaemic stroke despite direct oral anticoagulation - Purrucker, Jan; Meinel, Thomas Raphael; Wilson, Duncan; Xian, Ying; Wu, Teddy Y.; Seiffge, David (Stroke and vascular neurology, 2024)
Intravenous thrombolysis is not recommended in anticoagulated patients receiving direct oral anticoagulants (DOACs) and a recent intake within the last 48 hours in US and European guidelines. However, three observational studies now suggest safety of thrombolysis in patients with recent intake of DOACs, and thus support previous experimental data. In this perspective, the current evidence and practical consequences are discussed.
Gesehen am 17.06.2024